Music Theory for the 21st-Century Classroom - Hutchinson, Robert (Open textbook library., 2017)
Music Theory for the 21st–Century Classroom is an openly–licensed online four–semester college music theory textbook. This text differs from other music theory textbooks by focusing less on four–part (SATB) voiceleading and more on relating harmony to the phrase. Also, in traditional music theory textbooks, there is little emphasis on motivic analysis and analysis of melodic units smaller than the phrase. In my opinion, this led to students having difficulty with creating melodies, since the training they are given is typically to write a “melody” in quarter notes in the soprano voice of part writing exercises. When the assignments in those texts ask students to do more than this, the majority of the students struggle to create a melody with continuity and with appropriate placement of harmonies within a phrase because the text had not prepared them to do so. In Music Theory for the 21st–Century Classroom, students learn about motive, fragment, phrase, and subphrase, as well as types of melodic alteration like inversion, intervallic change, augmentation, diminution, rhythmic change, ornamentation, extension, and retrograde. By understanding motive and subphrase (also known as “phrase segment” or “phrase member”), I believe students will better understand the logic and construction of melodies, which will aid them in creating their own music. This text is meant to take the student from the basics of reading and writing pitches and rhythms through twelve–tone technique and minimalism over the course of four semesters. Whenever possible, examples from popular music and music from film and musical theater are included to illustrate melodic and harmonic concepts, usually within the context of the phrase.